'If they only knew what I know': Attitude change from education about 'fracking'. (3rd April 2017) - Evensen, Darrick
ABSTRACT: A simple explanation for why another's perspectives on unconventional gas development via hydraulic fracturing differ from one's own is that people are uninformed. Such an answer employs the deficit model of communication and understanding—shown for a quarter century to be inadequate for explaining public perceptions and behaviors. A more likely explanation, but far more challenging for an easy "fix", is that values fundamentally shape views. In autumn 2014, I taught an undergraduate course entirely on unconventional gas development (UGD) via hydraulic fracturing (often called "fracking"). I evaluated the effects of intensive education on attitudes about UGD by presenting my students with the same survey on the first and penultimate days of class. Overall attitudes changed little, despite substantial increases in self-reported knowledge and changes in beliefs about impacts associated with UGD. This poses a challenge for energy policies and regulation built off the assumption that additional education can readily change attitudes. I consider ways of approaching policy that respond to education's limited effects on attitudes about UGD.